FROM TRADITIONAL TO DIGITAL: TRANSFORMATION AND DYNAMICS OF CHANGE IN GONZO JOURNALISM - Erkaboeva Yakutkhan Mamasobirovna (Bright Mind Publishing, 2025)
This article analyzes the dynamics of the transformation and change of the gonzo style as it transitions from the traditional to the digital media landscape. The gonzo style emerged in Western journalism in the second half of the 20th century and was characterized by the author's personal position, emotional approach, and subjective expression. In the digital era, this style has expanded through social media, the blogosphere, and multimedia tools, acquiring new forms of expression. The article analyzes the global factors influencing the transformation of the gonzo style—technological development, changing audience needs, and the need for speed. From this perspective, gonzo journalism is viewed not as a genre, but as a style expressing the author's subjective involvement and personal approach. This transformation reveals new aspects of contemporary journalistic communication in terms of content and form.
Keywords: Gonzo journalism, transformation, digital information space, blogosphere, social networks, dynamics of change.